The Impact of Education on Cultural Identity - Howard Nicholas (Nusantara Science and Technology Proceedings, 2023)
In this paper, I argue that we need a wide understanding of culture and identity to understand how education shapes cultural identity, both positively and negatively. I present definitions of culture and identity that permit the complex relationships between education, culture, and identity to be explored and productively related to one another. I discuss how the teaching of both official and minority languages can contribute to the shaping of cultural identities. I reflect on how teachers can build on their students’ first and additional languages to develop inclusive and powerful cultural identities. Using examples from work in Australia, Vietnam, and Germany, I will look at how inclusive approaches to education have created spaces for new cultural identities. Central to my argument will be seeing the role of the teacher as an active decision-maker who uses physical, intellectual, and emotional spaces flexibly to create new learning opportunities.